PENERAPAN SISTEM INFORMASI GEOGRAFIS (SIG) PEMETAAN DAERAH RAWAN BANJIR TERKAIT DENGAN SUNGAI DI KABUPATEN PATI - Angga agustino maulana; Bambang agus herlambang; Ahmad khoirul anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
Flooding is a condition where the intensity of rainfall is very high and the water cannot be accommodated in the rivers in Pati Regency or the flow of water in the drainage channel is blocked, so that it overflows and inundates the surrounding area (flood plain). This research aims to analyze and determine the level of flood vulnerability based on Geographic Information Systems (GIS), especially in relation to areas concentrated along rivers in Pati Regency. The method used in this research uses primary data collection and secondary data by obtaining data in the form of documents, literature from related agencies or books that support research.